Pedagogi Strukmut: Smp Kristen Kotamobagu Medium dalam Literasi Pemajuan Budaya di Bolaang Mongondow - Ingkiriwang, Rivo; Kalalo, Jefry; Wales, Cornelius; Korompis, Christy (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2025)
The purpose of this study is to explore, describe, and analyze the significance of Mongondow cultural literacy at Kotamobagu Christian Junior High School as a medium for cultural advancement in Bolaang Mongondow. The research method used was descriptive qualitative, and data collection techniques included observation, interviews, literature review, and documentation study. The results of the study show that at Kotamobagu Christian Junior High School, literacy about Mongondow culture is minimal, so that access for educators (teachers) and students to obtain local knowledge about Mongondow culture is limited. In fact, the author found that the Kotamobagu Christian Junior High School Library only had books (dictionaries) on the Mongondow language, but books discussing what Bolaang Mongondow is and the history of Bolaang Mongondow were not available at the Kotamobagu Christian Junior High School Library. This has led to a decline in the epistemic knowledge of junior high school students at SMP Kristen Kotamobagu regarding the genealogy and history of Bolaang Mongondow.  Therefore, Strukmut pedagogy (mutualism structure) is needed as a complementary medium between pedagogy (Mongondow language) and Mongondow historical-cultural literacy pedagogy, so that cultural advancement in Bolaang Mongondow can be escalated.